Juliana Alžběta Sekerková ze Sedčic, převorka kláštera premonstrátek v Doksanech a spoluautorka válečných pamětí - Kuchařová, Hedvika (Bohemia Occidentalis Historica, 2019)
The essay focuses on the life and activities of Juliana Alžběta Sekerková of Sedčice. She was born 1615 in a noble family, probably non -Catholic. After the death of her parents she entered the Premonstratensian Canonry in Doksany (1636) where she later became prioress (1655). Her early life in the religious community was aff ected by the wartime’s violence and danger which repeatedly forced the whole convent to leave Doksany. As prioress Juliana Alžběta was involved in a controversy between Vincent, Abbot of Strahov and Cyrill, Provost of Doksany on the side of the latter. Wartime and the following years (to 1683) were described in her chronicle which continued a previous chronicle by provost Nicholas. She also authored „Vitae“ of the Doksany canonesses of her time.
Keywords: doksany

Klášter premonstrátek v Doksanech a Slánsko : Slánské rozhovory 2012 - Přibyl, Vladimír; Vychodil, Pavel; Přibylová, Dana (Vlastivědné muzeum Slaný, 2013)
Keywords: doksany

Poněkud hladová péče o památky. Zpráva o klášteře v Doksanech - Solař, Miloš (Dějiny a současnost : kulturně historická revue, 2011)
Keywords: doksany